Silage Quality of Rations Based on in situ Sorghum-Indigofera - Telleng, Malcky; Wiryawan, K.G.; Karti, P.D.M.H.; Permana, I.G.; Abdullah, L. (Pakistan Journal of Nutrition, 2017)
Background: Intercropping involves growing two or more crops on the same piece of land to produce rations for livestock, particularly ruminants. In this study, the silage quality of in situ rations produced from Sorghum intercropped with Indigofera was evaluated to determine which Sorghum variety produced the best silage. Methodology: The pH, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), ammonia-N (N-NH3), Volatile Fatty Acids (VFA) and total bacteria in silage for use in situ rations were verified. Experiments were conducted using a Completely Randomized Design (CRD) with three replications of three factors: (1) Sorghum variety (Patir-37 and Citayam-33), (2) Indigofera composition (30, 40 and 50% Indigofera ) and (3) Microbial inoculant (Lactobacillus plantarum, Lactobacillus casei and non-microbial inoculant). Data were analyzed using analysis of variance and HSD test. Results: For all rations tested, the pH and N-NH3 values indicated good ensilage. Rations that included the Sorghum variety Citayam-33 had lower pH and N-NH3 production relative to those with Patir-37. In whole crop silages, the inoculants did not significantly affect fermentation. Meanwhile, rations with higher amounts of Indigofera (up to 50%) had lower NDF and ADF. Conclusion: Together the results show that in situ rations made from intercropped Sorghum and Indigofera ensilage well and different compositions can be obtained directly from intercropped fields to produce rations that improve ruminant performance.